Low dark current Sb-based short-wavelength infrared photodetector - Li, Mingming; Cheng, Yifan; Zhang, Xiangyu; Zhang, Ye; Jiang, Dongwei; Song, Zhigang; Zheng, Wanhua (AIP advances, 2024)
We have theoretically and experimentally demonstrated the feasibility of achieving ultra-low dark current in CpBnn type detectors based on a double-barrier InAs/GaSb/AlSb type-II superlattice. By employing a structure that separates the absorption region and depletion region, the diffusion, recombination, tunneling, and surface dark currents of the photodetector (PD) have been suppressed. Experimental validation has shown that a detector with a diameter of 500 µm at a bias voltage of −0.5 V exhibits a dark current density of 2.5 × 10−6 A/cm2 at the operating temperature of 300 K. The development of PD with low dark current has paved the way for applications with high demands for low noise in the fields of gravitational wave detection and astronomical observation.